2017
DOI: 10.1297/cpe.26.73
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism among pediatric patients with type 1 diabetes mellitus, from patients’ characteristics to disease severity

Abstract: Abstract.We performed this study to evaluate the associations of hypothyroidism with clinical severity and the occurrence of diabetic ketoacidosis (DKA) at initial diagnosis among pediatric patients with type 1 diabetes mellitus (T1DM). 330 children with T1DM who referred to Diabetes Clinic were enrolled. The medical records were e valuated and a blood sample was drawn from patients for measuring thyroid function and antibodies, blood glucose, and glycated hemoglobin (HbA1C) levels. Hypothyroidism was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
4
12
0
Order By: Relevance
“…The high prevalence of low T3 syndrome, which is comparable to previous studies in T1DM, may be explained by the relatively high proportions of patients with DK or DKA (29.7%) in this study. TD including low T3 syndrome and hypothyroidism was more common in patients with DKA [3,[22][23][24]. The presence of low T3 syndrome was associated with poor glycemic control [3,22] and free thyroid hormones were correlated with the severity of DKA [22], which was in accordance with our ndings.…”
Section: Discussionsupporting
confidence: 85%
“…The high prevalence of low T3 syndrome, which is comparable to previous studies in T1DM, may be explained by the relatively high proportions of patients with DK or DKA (29.7%) in this study. TD including low T3 syndrome and hypothyroidism was more common in patients with DKA [3,[22][23][24]. The presence of low T3 syndrome was associated with poor glycemic control [3,22] and free thyroid hormones were correlated with the severity of DKA [22], which was in accordance with our ndings.…”
Section: Discussionsupporting
confidence: 85%
“…Among patients with T1DM, autoimmune thyroid disorder (AITD) is the most frequent autoimmune comorbidity that can manifest as autoimmune-induced hypothyroidism (Hashimoto's thyroiditis) or hyperthyroidism (Grave's disease) [ 5 ]. AITD is seen in 17%–30% of adults and in 25% of children with T1DM [ 2 , 6 8 ]. Patients who are positive for thyroperoxidase antibodies (anti-TPO) are 18 times more likely to develop hypothyroidism [ 2 ].…”
Section: Metabolic Dysfunctionsmentioning
confidence: 99%
“…In a study by Fatourechi et al, it was documented that children who had both TID and hypothyroidism had significantly higher HbA1c levels at enrollment, presented at younger age and most of them experienced DKA as the first presentation. 15 Balsamo et al, and Lin et al, also observed the association of severe metabolic derangement and impaired thyroid function in subjects with newly diagnosed TID. 6,16 There are many interpretations to explain the disease severity of T1D with thyroid dysfunction.…”
Section: Discussionmentioning
confidence: 90%